Agribusiness trade between Brazil and China: Pillars and opportunities - Marcelo José Braga Nonnenberg; Uallace Moreira Lima; Mateus Azevedo Araujo; Fernanda Pedrosa; Scarlett Queen Almeida Bispo (Institute for Applied Economic Research (ipea), 2021)
In this paper, we discuss the agricultural trade between Brazil and China. We select a set of key commodities and debate whether there are obstacles or opportunities to increase trade between the two economies. Following an institutional and historical analysis, we provide a statistical description of the recent history of Brazilian exports to China. We contrast the trade statistics with a set of indicators on the use of tariff and non-tariff measures and highlight which institutions are responsible to regulate the agricultural sector in Brazil. Our main findings support the relevance of the bilateral trade of agricultural products between Brazil and China. Still, a set of products can be classified as missed trade opportunities. We argue about the negative effects of preferential tariffs applied to other groups of countries. We can link the case of a subset of commodities to the incidence of non-tariff measures.
Keywords: F14; F13; Q17; O19; 330; agriculture; international trade; trade policy; Brazil; China